Association Between Reproduction and Postpartum Cow Health during Summer Months in Dairies Located in the Great Plains Region - L. Mendonca; A. Scanavez (Kansas Agricultural Experiment Station Research Reports, 2017)
Postpartum cow health has an impact on fertility of dairy cows, and impaired fertility in dairy herds ultimately influences profitability of dairy farms. During summer months, postpartum cow health and reproductive performance are affected in dairies located in the Great Plains region. The goal for this study was to evaluate farm-level associations between reproductive efficiency and postpartum cow health in dairy herds located in the Great Plains region. Data from June to August of 2010 to 2016 from 18 herds located in Colorado, Kansas, Oklahoma, Nebraska, and Texas were extracted. Overall pregnancy per AI was used as the measure of reproductive efficiency, and percentage of stillbirth cases, mastitis within 21 d after calving, and cows sold and cows dead within 60 d after calving were used to evaluate postpartum cow health and performance. Using the intercept and slopes from a logistic regression model, a transition cow index was created. Poor herd fertility, pregnancy per AI<30%, was associated with percentage of stillbirth events and postpartum mastitis cases. In 93% of the instances that herds had pregnancy per AI<30%, transition cow index was less than 0. This study demonstrates that fertility is associated with transition cow performance at the herd level during summer months in dairies located in the Great Plains region.
Keywords: reproduction; postpartum cow health; heat stress